THE EFFECT OF THE USE OF MOBILE COMMUNICATION DEVICES ON STUDENT LEARNING OUTCOMES - Setiawan, Aan; Ismail, M. Jen (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
The results of the study prove that the effect of the use of mobile phone communication devices on the learning outcomes of students in the subject of moral beliefs at Madrasah Aliyah in Banggai Regency was obtained by testing the hypothesis between variable X (mobile phone use) and variable Y (learning outcomes) where each variable was tested with its validity and reliability. The data obtained was then analyzed using the Simple Linear Regression equation. The model of a simple linear regression equation produced is learning outcomes (Y) = 71.242 which means that the compensation variable (X) has a positive influence on the dependent variable of learning outcomes (Y) the value of the correlation coefficient (Multiple R), showing that compensation will cause a positive increase in learning outcomes. The value of the determination coefficient (R. Square) shows that the change in compensation will affect learning outcomes The value of the variable value of mobile phone use (X) is greater than the ttable. The value of sig. t is less than 0.05. These results show that partially the variable of Mobile Phone Use has a significant influence on the variable of Learning Outcomes.